(untitled) (Pokhara Engineering College Journal, 2026)
The study presents the seismic vulnerability assessment of plan irregular reinforced concrete framed building. At PEC, there are a total of 5 blocks among which Block-B, established in 2000 AD was selected for detailed assessment due to its structural irregularities. The assessment started with visual inspection using FEMA guidelines, which revealed undersized members, poor concrete quality, irregular plan layout, torsional irregularity, and visible deterioration. Non‑destructive tests (Ultrasonic Pulse Velocity and Rebound Hammer) confirmed good internal concrete integrity but weak surface strength. To understand the building’s seismic performance more clearly, a structural model was developed in ETABS v22.5 following NBC 105:2020. The analysis showed that 130 members failed seismic checks, including torsional irregularities, storey drift, and displacement limits. Based on these findings, a hybrid retrofitting plan was proposed combining concrete jacketing for columns and beams, steel jacketing for selected beams, and the addition of reinforced concrete shear walls. Post‑retrofitting analysis showed clear improvements in displacement, drift, and torsional behavior bringing the building’s performance closer to national seismic safety standards. From an economic point of view, retrofitting of the building is far more affordable than demolishing and constructing a new one. In other words, retrofitting required only 15.6% of the replacement cost making it the practical choice. Overall hybrid retrofitting stands out as both technically effective and economically practical.